The Role of Family Structure and Family Processes on Adolescent Problem Behavior. Issue 1 (2nd January 2022) - Childs, Kristina K.; Brady, Caitlin M.; Cameron, Alesha L. J.; Kaukinen, Catherine
ABSTRACT: We examined the impact of family structure and family processes on engagement in multiple and co-occurring problem behaviors during adolescence (delinquency, substance use, risky sexual behavior, and truancy) while accounting for key risk factors (attachment to school, antisocial peers, self-control, and residential stability) for antisocial behavior. Using data from Waves 1 and 2 of the National Longitudinal Study of Adolescent to Adult Health (n = 9, 992), latent class analysis identified classes of youth based on engagement in multiple forms of problem behavior. Multinomial logistic regression was then employed to test the direct and indirect effects of family structure on family processes and placement in the latent classes. Significant differences in family processes and latent class membership were identified across categories of family structure except when comparing across two types of single biological mother households (with children from one father and multipartnered fertility families). Family processes, self-control, and having antisocial peers reduced the effects of family structure on latent class membership.